Uso de tecnologias como ferramenta de ensino da matemática financeira: revisão bibliográfica - MACEDO, Rubem Gilson Correa de (2024)
This paper discusses how technology is used to teach financial mathematics to students in the second segment of elementary school. The study discusses how students' understanding and application of financial ideas can be improved through the use of technology in an environment where financial education is increasingly important. Based on a survey of more recent literature published between the years 2020 to 2023, the research highlights a number of current approaches investigating the integration of technology in education, including the use of Excel, digital games, videos and interactive platforms. These digital technologies have been highlighted by many researchers who show how technology can contextualize financial ideas and make them more understandable and applicable by associating them with real-life scenarios. The study highlights the use of these digital technologies, as well as how they encourage students to actively participate in the learning process, creating a solid foundation for the development of the study of financial mathematics.